Effect of e-service quality, consumer trust, and brand image on the loyalty of BCA m-banking users - Johan; Nainggolan, Nora Pitri (Institute of Computer Science (IOCS), 2025)
Technology continues to advance with the advent of the internet. One technology that has continuously developed alongside the internet is mobile banking. The increasing sophistication of mobile banking has encouraged Indonesians to conduct transactions through this channel. This research uses a single mobile banking service as its object: BCA Mobile, due to its leading position in the mobile banking sector. The aim of this research is to determine the profile of e-service quality, consumer trust, and brand image of this mobile banking service. The research method employed is quantitative descriptive, utilizing documentation and questionnaire distribution as data analysis techniques. This study uses probability sampling methods. Cochran's formula was used for sample selection due to the large and unknown population size. The population used in this research comprises Indonesian citizens who have used or are currently using BCA Mobile banking. The research analyzes validity, multicollinearity regression, reliability, coefficient of determination, and hypotheses. Data analysis employs multiple linear regression analysis, while hypothesis testing utilizes t-tests and F-tests with SPSS version 25. The results show that the dominant respondents are aged 18-25, female, and students. This research is expected to contribute to marketing management and consumer behavior studies regarding consumer loyalty to mobile banking. Furthermore, this research can serve as a reference for banks providing mobile banking services to develop strategies for improving service quality and increasing user satisfaction. The study indicates that consumer trust and brand image have a positive and significant impact on the loyalty of mobile banking users, while e-service quality does not have a positive and significant impact on the loyalty of mobile banking users